Evil dead (2013) [videorecording (DVD)] - Alvarez, Fede. 1978-; Levy, Jane, 1989-; Fernandez, Shiloh, 1985-; Pucci, Lou Taylor, 1985-; Lucas, Jessica, 1985- (Sony Pictures Home Entertainment, 2013)
In the much-anticipated remake of the 1981 cult-hit horror film, five twenty-something friends become holed up in a remote cabin. When they discover a Book of the Dead, they unwittingly summon up dormant demons living in the nearby woods, which possess the youngsters in succession until only one is left intact to fight for survival.